Предмет: Алгебра,
автор: manizgajsnj
решите уравнение (x-2)^2+3(x-2)^2-10=0
Ответы
Автор ответа:
0
Ответ:
x=3.6
x=0.4
Объяснение:
(х-2)²+3(х-2)²-10=0
Раскроем скобки
Получаем:
х²-4х+4+3(х²-4х+4)-10=0
х²-4х+4+3х²-12х+12-10=0
4х²-16х+6=0
D=b²-4ac=256-96=160
x=16+12.7/8=3.6
x=16-12.7/8=0.4
Похожие вопросы
Предмет: Русский язык,
автор: atrykov1234
Предмет: Русский язык,
автор: полина1125
Предмет: Английский язык,
автор: Аноним
Предмет: Обществознание,
автор: Kamilya2007
Предмет: Музыка,
автор: chnkvvv